1990
DOI: 10.1002/jsfa.2740520407
|View full text |Cite
|
Sign up to set email alerts
|

Apparent and true ileal digestibility of amino acids and nitrogen balance measured in pigs with ileo‐rectal anastomosis or T‐cannulas, given a diet containing peas

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…The mean endogenous amino acid flows for the protein-free fed pigs in the present study were similar to those reported by Sauer et al (1977), Taverner et al (1981), Green et al (1987, Furuya and Kaji (1989), Wang and Fuller (1989), Leterme et al(1990) and Butts et al(1992a. High levels of proline and glycine have been frequently reported in endogenous ileal amino acid excretions determined under protein-free alimentation.…”
Section: Discussionsupporting
confidence: 91%
“…The mean endogenous amino acid flows for the protein-free fed pigs in the present study were similar to those reported by Sauer et al (1977), Taverner et al (1981), Green et al (1987, Furuya and Kaji (1989), Wang and Fuller (1989), Leterme et al(1990) and Butts et al(1992a. High levels of proline and glycine have been frequently reported in endogenous ileal amino acid excretions determined under protein-free alimentation.…”
Section: Discussionsupporting
confidence: 91%
“…The RMSEP is low (<4.9%). (Leterme et al, 1990;Maillard et al, 1990;Jansman et al, 1993;Fan and Sauer, 1994;Van Barneveld and Batterham, 1994;Canibe and Bjorn, 1997;Hess et al, 1998;Fan and Sauer, 1999;Grosjean et al, 2000;Hess et al, 2000;Mariscal landin et al, 2002;Owusu-Asiedu et al, 2002;Kasprowicz and Frankiewicz, 2004;Jezierny et al, 2011;Chilomer et al, 2013 For models developed from experimental diet composition, the d value was larger (7%) for histidine whereas varying between −1.05% and 1.36% for the other EAA (Table 12). The intercept was not significant different for 0 and the slope was equal to 1 for all EAA.…”
Section: Evaluation Of Model Performancementioning
confidence: 92%
“…(Sauer et al, 1977;Cousins et al, 1981;Sauer et al, 1981;Tanksley et al, 1981;Taverner et al, 1981;Walter et al, 1981;Rudolph et al, 1983;Anderson et al, 1984;Adeola et al, 1986;Chang et al, 1987;Green and Kiener, 1989;Batterham et al, 1990;Leterme et al, 1990;Haydon and Hobbs, 1991;Herkelman et al, 1990;Rodhouse et al, 1992;Jansman et al, 1993;Mosenthin et al, 1993;Fan and Sauer, 1994;Kim et al, 1994;Marty and Chavez, 1994;Van Barneveld and Batterham, 1994;Yin et al, 1994;Fan et al, 1995a,b;Adeola and Orban, 1995;Fan et al, 1996a,b;Canibe and Bjorn, 1997;Bellaver and Easter, 1998;De Lange et al, 1998;Grala et al, 1998;Hess et al, 1998;Van Barneveld et al, 1998;Woodworth et al, 1998;Reverter et al, 1999;Stein et al, 1999;Kim et al, 2000;O'Quinn et al, 2000;Salgado et al, 2001;Woodworth et al, 2001;Li et al, 2002;Mariscal landin et al, 2002;Moeser et al, 2002;…”
Section: Tablementioning
confidence: 97%
See 2 more Smart Citations